Violence in American Public Schools: Causes and Effects - بريبش، وفاء, بوروبة، سمية (University of El-oued, 2022)
العنف المدرسي ظاهرة خطيرة انتشرت في جميع أنحاء الولايات المتحدة الأمريكية خلال السنوات الأخيرة. تهدف هذه الرسالة إلى التعرف على الأسباب والتأثيرات الرئيسية لهذه الظاهرة. يعتمد النهج النوعي المعتمد لهذه الدراسة على تحليل الوثائق المتاحة من أجل الحصول على رؤية أعمق لهذه القضية وكشف جذورها. تربط نتائج الدراسة أسباب العنف في المدارس العامة الأمريكية بظروف تاريخية وسياسية واجتماعية اقتصادية مختلفة ، بما في ذلك الاختلافات الدينية والعرقية والظلم الاجتماعي والاقتصادي ووسائل الإعلام والعنف السياسي. تشمل آثار العنف المدرسي انتشار الجريمة ، وإيذاء الطلاب والمعلمين والموظفين ، وانخفاض التحصيل الدراسي للطلاب ، وأداء المعلمين غير الفعال. وتختتم الدراسة ببعض التوصيات العملية حول كيفية الحد من معدل العنف المدرسي ، وتعزيز سياق التعلم ، وحماية الأجيال القادمة. School violence is a serious phenomenon which spread all over the United States of America during the recent years. This dissertation aims to identify the main causes and effects of this phenomenon. The qualitative approach adopted for this study draws on the analysis of the available documents in order to obtain deeper insight into this issue and uncover its roots. Findings of the study link the causes of violence in American public schools to different historical, political and socio-economic conditions, including religious and ethnic differences, socio-economic injustice, media, and political violence. The effects of school violence involve the proliferation of crime, victimisation of the students, the teachers, and the staff, low students’ academic achievement, and ineffective teachers’ performance. The study concludes with some practical recommendations on how to reduce the rate of school violence, enhance the learning context, and protect future generations.
Keywords: العنف المدرسي في الولايات المتحدة ، الأسباب ، الآثار ، الطلاب ، التحصيل الدراسي; school violence in US, causes, effects, students, academic achievement